Benefits of Integrating Wireless Technology with Hearing Instruments - Spangler, Carrie (Seminars in Hearing, 2014)
Audiologists are faced with patient demand to improve understanding of speech in difficult listening environments. Patients with hearing loss typically report difficulty understanding in noise, on the phone, and while watching television. Hearing technology advancements give patients options to connect wirelessly to everyday technology, thus improving patient satisfaction. The continuous rapid boom of everyday technology challenges audiologists to meet the listening and fitting needs of patients. This article will explore the current literature for integrating hearing instruments with current technology sources that promote access to communication in our communities as well as the importance of addressing patient self-efficacy skills. Examples of situations and connectivity solutions that benefit pediatric and adult populations, including pros and cons of integrating technology wirelessly to devices, are discussed.
Keywords: Wireless hearing technology; unified communication; hearing loss; self-efficacy